Двухточечная задача для систем, удовлетворяющих условию управляемости со скобками Ли второго порядка - Грушковская, В.В.; Зуев, А.Л. (Нелінійні коливання, 2015)
Дослiджується двоточкова задача керування для лiнiйних за керуванням систем. Клас систем, що розглядається, задовольняє умову керованостi з дужками Лi до другого порядку включно. Для розв’язання поставленої задачi використовуються тригонометричнi полiноми, коефiцiєнти яких обчислюються за допомогою розвинень розв’язкiв системи в ряд Вольтерра. Запропоновано зведення двоточкової задачi керування до розв’язання системи алгебраїчних рiвнянь. Доведено, що така система локально має принаймнi один дiйсний розв’язок. Запропонований метод побудови керуючих функцiй проiлюстровано на кiлькох прикладах. We study a two-point control problem that is control linear. The class of the problems under consideration satisfies a controllability condition with Lie brackets of order up to two inclusive. To solve the problem, we use trigonometric polynomials the coefficients of which are calculated by expanding solutions into Volterra series. The proposed method permits to reduce the two-point control problem to a system of algebraic equations. We prove that such an algebraic system locally has at least one real solution. The proposed method for constructing control functions is illustrated with several examples.